Enhancement of host resistance against Trypanosoma cruzi infection by the immunoregulatory agent muramyl dipeptide. - Kireszenbaum, F (1979)
N-acetylmuramyl-L-alanyl-D-isoglutamine (muramyl dipeptide [MDP]) enhanced resistance against Trypanosoma cruzi infection in mice. This effect was evidenced by significant reductions in both parasitemias and mortality rates and increased survival time in MDP-treated animals compared with untreated infected mice. MDP effectively augmented host resistance when administered in any one of the following ways: (i) continuous subcutaneous release from an osmotic minipump for a 7-day period starting 2 days before infection; (ii) as a single dose of 0.5 mg injected intraperitoneally 48 h before infection; or (iii) injected intraperitoneally at 48-h intervals during the first 16 days after infection. CBA/J mice, which exhibit very low, insignificant augmentation of reticuloendothelial activity by MDP but are susceptible to its adjuvant effect, failed to manifest enhancement of resistance to T. cruzi infection when treated with MDP under regimens that cause increased resistance in other mouse strains. These results suggest that MDP enhances resistance against T. cruzi infection by stimulating the activity of the phagocytic cells of the host. Adjuvant effect appears to play either a less significant role or no relevant role, except when MDP is administered repeatedly after infection.